INTERNALISASI NILAI-NILAI POLITIK ISLAM DALAM MEMBANGUN BUDAYA POLITIK YANG SANTUN DAN BERINTEGRITAS - M. Dahlan R (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2026)
Strengthening a political culture of decency and integrity is an important need in a democratic society, especially amid increasing political polarization, the practice of political pragmatism, and a low ethical standard in public communication. This community service activity aims to internalize Islamic political values, namely justice (‘adl), deliberation (shura), trust, and responsibility as the foundation for the formation of an ethical political culture. The method used is participatory training through interactive lectures, reflective discussions, case studies, and deliberation simulations involving the community as active participants. The activity began with mapping the needs to determine participants’ initial level of understanding, then continued with the delivery of materials and participatory dialogue practices and ended with joint reflection. The results of the activity showed an increase in participants’ understanding of Islamic political ethics and a growing awareness of applying the values of justice, deliberation, trust, and responsibility in social life. The internalization of values through a dialogical approach has been shown to encourage a more open, tolerant, and responsible attitude toward political differences. Thus, this activity shows that strengthening Islamic political values can be a relevant educational strategy for building a polite, integrity-based political culture in society.